Infrastructure, planning and the command of time. (December 2016) - Marshall, Tim; Cowell, Richard
Governments in many countries have sought to accelerate the time taken to make decisions on major infrastructure projects, citing problems of 'delay'. Despite this, rarely has the time variable been given careful empirical or conceptual attention in decision-making generally, or in infrastructure decision-making specifically. This paper addresses this deficit by analysing decision-making on two categories of major infrastructure in the UK – transport and electricity generation – seeking both to generate better evidence of the changes to decision times in recent decades, and to generate insights from treating time as resource and tracking its (re)allocation. We find that reforms introduced since 2008 have done relatively little to alter overall decision times, but that there are marked and revealing changes to the allocation of time between decision-making stages. While public planning processes have their time frames tightly regulated, aspects led by developers (e.g. pre-application discussion) are not; arranging finance can have a bigger effect on project time frames, and central government retains much flexibility to manage the flow of time. Speed-up reforms are also sectorally uneven in their reach. This indicates how arguments for time discipline falter in the face of infrastructure projects that remain profoundly politicised.